2021
DOI: 10.1155/2021/6686745
|View full text |Cite
|
Sign up to set email alerts
|

Applying Deep Learning Methods on Time‐Series Data for Forecasting COVID‐19 in Egypt, Kuwait, and Saudi Arabia

Abstract: The novel coronavirus disease (COVID-19) is regarded as one of the most imminent disease outbreaks which threaten public health on various levels worldwide. Because of the unpredictable outbreak nature and the virus’s pandemic intensity, people are experiencing depression, anxiety, and other strain reactions. The response to prevent and control the new coronavirus pneumonia has reached a crucial point. Therefore, it is essential—for safety and prevention purposes—to promptly predict and forecast the virus outb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
1
30
0
Order By: Relevance
“…By the end of March 2021, Saudi Arabia had confirmed cases of more than 390,000 and more than 6500 deaths. This study is in line with other COVID-19 studies that have been conducted based on region-specific data, such as [8] in Brazil, [26] in Romania, and [27] in Egypt, Kuwait, and Saudi Arabia.…”
Section: Introductionsupporting
confidence: 91%
“…By the end of March 2021, Saudi Arabia had confirmed cases of more than 390,000 and more than 6500 deaths. This study is in line with other COVID-19 studies that have been conducted based on region-specific data, such as [8] in Brazil, [26] in Romania, and [27] in Egypt, Kuwait, and Saudi Arabia.…”
Section: Introductionsupporting
confidence: 91%
“…Their application of an ARIMA model with different lags (1,0,2), (1,1,1), (1,1,3) showed that an ARIMA model with lag (1,1,1) was better than the others and gave scores of R2 (0.96) and RMSE (341) in that period. Nahla et al [68] presented two deep learning approaches (LSTM and GRU) to predict COVID-19 infection in Egypt, Kuwait, and Saudi Arabia from 1 May 2020 to 12 June 2020. The empirical results showed that the LSTM model achieved the highest percentages for the evaluation metrics MAPE (0.445), RMSE (29.8), and MAE (28.0).…”
Section: Related Workmentioning
confidence: 99%
“…Coronavirus disease (COVID-19) is considered one of the most confrontational pandemics causing severe danger to humanity in the twenty-first century due to its progression, infection, spread, and mortality rate worldwide [28] . Till July 2021, the COVID-19 confirmed cases over the world were 190 million cases including 4.1 million deaths.…”
Section: Introductionmentioning
confidence: 99%